Photoluminescence of crystalline and disordered BTO : Mn powder: Experimental and theoretical modeling - Gurgel, M. F. C.; Espinosa, J. W. M.; Campos, A. B.; Rosa, I. L. V.; Joya, M. R.; Souza, A. G.; Zaghete, M. A.; Pizani, P. S.; Leite, E. R.; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Elsevier B.V., 2007)
Disordered and crystalline Mn-doped BaTiO3 (BTO:Mn) powders were synthesized by the polymeric precursor method. After heat treatment, the nature of visible photoluminescence (PL) at room temperature in amorphous BTO:Mn was discussed, considering results of experimental and theoretical studies. X-ray diffraction (XRD), PL, and UV-vis were used to characterize this material. Rietveld refinement of the BTO:Mn from XRD data was used to built two models, which represent the crystalline BTO:Mn (BTO:Mn,) and disordered BTO:Mn (BTO:Mn-d) structures. Theses models were analyzed by the periodic ab initio quantum mechanical calculations using the CRYSTAL98 package within the framework of density functional theory at the B3LYP level. The experimental and theoretical results indicated that PL is related with the degree of disorder in the BTO:Mn powders and also suggests the presence of localized states in the disordered structure. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: photoluminescence; periodic model; ab initio; Mn-doped BaTiO3